Blocking Opioid Receptors in a Songbird Cortical Region Modulates the Acoustic Features and Levels of Female-Directed Singing - Kumar, Sandeep; Mohapatra, Alok Nath; Pundir, Arvind Singh; Kumari, Mukta; Din, Uzma; Sharma, Sudha; Datta, Atanu; Arora, Vasav; Iyengar, Soumya (Frontiers in Neuroscience, 2020)
The organization of the anterior forebrain pathway (AFP) of songbirds important for context-dependent singing is similar to that of cortical basal ganglia loops (CBG) in mammals, which underlie motor behaviours including vocalization. Since different components of the AFP express high levels of µ-opioid receptors (µ-ORs) as do CBG loops, songbirds act as model systems to study the role of opioid modulation on vocalization and the motivation to sing. The AFP in songbirds includes the cortical/pallial region LMAN (lateral magnocellular nucleus of the anterior nidopallium) which projects to Area X, a nucleus of the avian basal ganglia. In the present study, microdialysis was used to infuse different doses of the opioid antagonist naloxone in LMAN of adult male zebra finches. Whereas all doses of naloxone led to significant decreases in the number of FD (female-directed) songs, only100 and 200ng/ml of naloxone affected their acoustic properties. The decrease in FD song was not accompanied by changes in levels of attention towards females or those of neurotransmitters (dopamine, glutamate and GABA) in LMAN. An earlier study had shown that similar manipulations in Area X did not lead to alterations in the number of FD songs but had significantly greater effects on their acoustic properties. Taken together, our results suggest that there are reciprocal effects of OR modulation on cortical and basal ganglia components of the AFP in songbirds.